A universal method for prussian blue and tunnel oxide composite based on multi-dislocation plane regulation and its application in sodium ion battery

CN118183856BActive Publication Date: 2026-10-23WENZHOU UNIV CARBON NEUTRALITY TECH INNOVATION RES INST
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410421244.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-09
Publication Date
2026-10-23
Estimated Expiration
2044-04-09

AI Technical Summary

Technical Problem

[0006]为解决现有技术中隧道氧化物的首圈充电比容量低、与硬碳负极匹配性差等不足,本发明的目的在于提供一种基于多位错晶面调控普鲁士蓝与隧道氧化物复合材料的普适方法,该复合材料能协同改善钠离子电池的首圈库伦效率、与硬碳负极良好匹配和较低的生产成本

Benefits of technology

[0020]1.本发明将富钠型普鲁士蓝NaxMy[N(CN)6]z·nH2O与贫钠型Na0.44MnαTM1-αO2进行复合,采用低成本的普鲁士蓝来提高Na0.44MnαTM1-αO2在首圈充放电过程中的活性钠含量,大幅提高复合材料的首圈充电比容量,使其具有理想的首圈库伦效率并在全电池中与硬碳负极的匹配性高。此外,该复合材料充分利用Na0.44MnαTM1-αO2的高放电比容量以及普鲁士蓝较高的首圈充电比容量、良好倍率性能的优点,同时克服单独利用两种材料时的不足,实现协同提高钠离子电池的首圈库伦效率、放电比容量、能量密度、倍率性能和循环性能,在钠离子电池的实际生产中表现出全面的性能优势和成本效益。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118183856B_ABST
    Figure CN118183856B_ABST
Patent Text Reader

Abstract

This invention discloses a universal method for controlling Prussian blue and tunnel oxide composite materials based on multiple dislocation crystal planes and its application in sodium-ion batteries. The composite material includes tunnel oxide Na... 0.44 Mn α TM 1‑α O2 and Prussian blue Na with multiple dislocation planes x M y [N(CN)6] z ·n H2O. Wherein, Na... x M y [N(CN)6] z · n The M / N atoms in H2O partially replace Na. 0.44 Mn α TM 1‑α The Mn / TM atoms in O2 promote the formation of a new symbiotic phase in the composite material. On the one hand, this composite cathode material fully utilizes the advantages of both to achieve complementary performance of sodium-ion batteries; on the other hand, it innovatively prepares Na... x M y [N(CN)6] z ·n H₂O, with its internal localized stress and distortion, generates a symbiotic phase during high-energy ball milling. This significantly improves the first-cycle coulombic efficiency of the composite material, making it well-matched with hard carbon anodes in full cells. Furthermore, it comprehensively enhances discharge capacity, rate capability, cycle life, and cost advantages, bringing considerable economic benefits to the practical application of high-performance sodium-ion batteries. This invention can also be extended to the optimization of other oxides, demonstrating good versatility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of energy material preparation and sodium-ion batteries, specifically involving a universal method for controlling Prussian blue and tunnel oxide composite materials based on multiple dislocation crystal planes and its application in sodium-ion batteries. Background Technology

[0002] With the increasing market demand for grid-scale energy storage systems, there is an urgent need to develop advanced energy storage technologies with high conversion efficiency and cost-effectiveness. Sodium-ion batteries possess significant advantages such as abundant and widely distributed sodium resources, low cost, environmental friendliness, and an intercalation storage mechanism similar to lithium-ion batteries, making them promising candidates for next-generation stationary electrochemical energy storage applications. To achieve high-performance sodium-ion batteries for practical applications, exploring cathode materials that are simple to synthesize, have excellent performance, and are well-matched with the anode plays a crucial role in reducing production costs and improving battery performance.

[0003] To date, commercially promising cathode materials mainly include layered oxides, Prussian blue analogs, polyanionic compounds, and organic frameworks. Layered transition metal oxides are considered one of the most promising cathode materials due to their high theoretical capacity, suitable operating potential, low cost, and ease of industrial-scale production. Based on the Na coordination environment and oxygen layer stacking arrangement, layered transition metal oxides generally exhibit various crystal structures, including P2, O2, P3, O3, and tunnel structures. Among these, O3 belongs to the sodium-rich system, while the other structures belong to the sodium-poor system. Na... 0.44 Mn α TM 1-α O2, due to its abundant large S-shaped tunnels, can be found in Na + The intercalation / deintercalation process alleviates lattice strain and volume changes, thus exhibiting excellent cycle stability. However, due to Na... 0.44 Mn α TM 1-α O2 belongs to a sodium-poor system, with a low initial available sodium content, resulting in a low first-cycle charge specific capacity and poor matching with the hard carbon anode, which seriously hinders the practical application of sodium-ion batteries. Therefore, improving the first-cycle charge specific capacity is an important factor in improving the performance of sodium-ion batteries.

[0004] To address these issues, researchers have largely employed doping and coating strategies. For instance, patent application CN115498156A discloses a magnesium-doped ternary layered cathode material for sodium-ion batteries and its preparation method. After changing the Mg doping content, the material's first-cycle coulombic efficiency increased from 67% to 78%, with charge compensation provided by anion valence changes during charge and discharge. Patent CN116364898B discloses a sodium-ion cathode material, its preparation method, and a sodium-ion battery. An O3 phase coating layer is formed on the surface of the P2 phase bulk material, improving the material's specific capacity. The resulting cathode material achieves a first-cycle efficiency of 90%, matching that of hard carbon anodes. However, both of these strategies have limitations. Doping generally introduces additional ions or atoms, occupying positions originally used for charge storage, thus reducing the effective sites available for charge storage or causing reactions with electrolyte components, leading to a decline in battery performance. Meanwhile, the uneven distribution of the coating layer and its gradual fragmentation and detachment during cycling can severely affect the cycle life of the cathode material, limiting the practical application of sodium-ion batteries. Considering the limitations of the aforementioned doping and coating methods, this study employs a composite method to comprehensively utilize the advantages of different materials and implement flexible design. Therefore, finding a composite material that can effectively improve the first-cycle specific capacity of tunnel oxide batteries is particularly crucial.

[0005] Therefore, this invention creatively combines a sodium-rich Prussian blue with a sodium-poor Na+ crystal with a sodium-poor Na+ crystal. 0.44 Mn α TM 1-α O2 reacts with Prussian blue, which possesses a unique open-frame structure, a large ion tunnel structure, and abundant sodium storage sites, to form a complex with Na. 0.44 Mn α TM 1-α O2 composites can significantly increase the active sodium content of the composite cathode, allowing it to be well-matched with the hard carbon anode in a full cell, improving battery performance and reducing production costs. Meanwhile, Na... 0.44 Mn α TM 1-α The good stability of O2 can also alleviate the structural collapse and capacity decay of Prussian blue to some extent. The combination of the two materials can not only make up for the shortcomings of the single material, but also synergistically give full play to the advantages of both. In addition, the composite material also generates a novel symbiotic phase, which exhibits better first-cycle coulombic efficiency, rate performance and cycle performance, providing guidance for promoting the industrial production and application of cathode materials, and helping to promote the development and application of sodium-ion batteries in energy storage and other application fields. Summary of the Invention

[0006] To address the shortcomings of existing technologies, such as low first-cycle charging specific capacity of tunnel oxide and poor matching with hard carbon anodes, the present invention aims to provide a universal method based on multi-dislocation crystal plane modulation of Prussian blue and tunnel oxide composite materials. This composite material can synergistically improve the first-cycle coulombic efficiency of sodium-ion batteries, achieve good matching with hard carbon anodes, and reduce production costs.

[0007] The present invention also aims to provide a positive electrode and a sodium-ion battery. The positive electrode is prepared from the above-mentioned composite material, and the sodium-ion electrode is assembled from the positive electrode. The final result is a high-performance sodium-ion battery with excellent first-cycle coulombic efficiency, discharge specific capacity, energy density, rate performance and cycle performance, as well as a cost-effective synthesis method suitable for actual production and applicable to other oxides.

[0008] To achieve the above objectives, the present invention employs the following technical solution: a universal method for controlling Prussian blue and tunnel oxide composite materials based on multiple dislocation crystal planes and its application in sodium-ion batteries, wherein the chemical formula of the composite material is Na. 0.44 Mn α TM 1-α O2@Na x M y [N(CN)6] z ·n In the presence of H2O, the M / N atoms in the Prussian blue partially replace the Mn / TM atoms in the tunnel oxide, promoting the formation of a new symbiotic phase in the composite material. The specific synthesis steps are as follows:

[0009] S1: Weigh sodium carbonate and transition metal oxide according to a certain stoichiometric ratio, mix and grind thoroughly for 30-60 minutes, fill into a mold and press into 2-5 mm round discs, place the discs in a muffle furnace and calcine at 800-1000 ℃ for 10-20 hours to obtain the Na. 0.44 Mn α TM 1-α O2, where 0 ≤ α ≤ 1;

[0010] S2: Dissolve the transition metal sulfate and sodium citrate in 50-200 mL of deionized water at a specific molar ratio and stir for a certain time to prepare solution A. Dissolve the transition metal complex and sodium citrate in 50-200 mL of deionized water at a specific molar ratio and stir for a certain time to prepare solution B. Then, quickly transfer solutions A and B to a constant pressure dropping funnel and a three-necked flask, respectively, and add solution A dropwise to solution B. Stir the mixed solution at 500-1200 rpm for a certain time and continue aging. After aging, collect the precipitate by centrifugation at 800-1500 rpm and wash it 3-5 times with deionized water and ethanol, respectively. Finally, dry the washed precipitate in a vacuum oven at 100-150 ℃ for 10-20 h to obtain the multi-site dislocation-faceted Prussian blue Na. x M y [N(CN)6] z ·n H2O;

[0011] S3: Weigh out Na according to a certain mass ratio 0.44 Mn α TM 1-α O2 and Na x M y [N(CN)6] z ·n H2O is mixed with the material in a ball mill at a certain ball-to-material ratio and milled at 200-500 rpm for 2-8 hours to obtain Na. 0.44 Mn α TM 1-α O2@Na x M y [N(CN)6] z · n H2O.

[0012] Preferably, the transition metal element TM in the transition metal oxide in step S1 is any one of the elements in Groups IⅤB-ⅠB of the third period, or a mixture of multiple elements in stoichiometric ratio, with Mn being the most preferred. The stoichiometric ratio of sodium carbonate to the transition metal oxide is based on Na… 0.44 Mn α TM 1-α The molar ratio of the chemical composition of O2, in which sodium carbonate is in excess by 7-20%.

[0013] Preferably, the transition metal sulfate, transition metal complex, and Na mentioned in step S2 x M y [N(CN)6] z ·nThe transition metal element M / N in H2O is any one of the elements in Groups IIIB-IIB of the third period, or a mixture of multiple elements in stoichiometric ratios, and the ligand of the transition metal complex is CN. - NO3 - CH3COO - Any one of the above or a mixture of multiple substances in stoichiometric ratios, wherein CN is the most preferred. - .

[0014] Preferably, in step S2, the molar ratio of the transition metal sulfate to sodium citrate is 1:0.8-1:3.5, and the stirring time is 1-5 h; the molar ratio of the transition metal complex to sodium citrate is 1:1.2-1:4.3, and the stirring time is 0.5-3 h; and the Prussian blue Na... x M y [N(CN)6] z ·n 0.53≤ in H2O x ≤2.68, 0.65≤ y ≤1.75, 0.85≤ z ≤1.35, 2.7≤ n ≤4.6.

[0015] Preferably, in step S2, the dropping rate of solution A is controlled at 1-10 drops / minute, the stirring time of the mixed solution is 5-10 h, and the aging time is 10-16 h.

[0016] Preferably, the Na mentioned in step S3 0.44 Mn α TM 1-α O2 and Na x M y [N(CN)6] z ·n The mass ratio of H2O is 2:1-10:1, and the ball-to-material ratio is 6:1-15:1.

[0017] This invention provides a positive electrode sheet comprising Na as described in any of the above technical solutions. 0.44 Mn α TM 1-α O2@Na x M y [N(CN)6] z ·n H2O composite materials, conductive agents, and binders.

[0018] The present invention also provides a sodium-ion battery, comprising the positive electrode, separator, electrolyte and negative electrode as described above.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. This invention utilizes sodium-rich Prussian blue (Na) x M y [N(CN)6] z ·n H2O and sodium-deficient Na 0.44 Mn α TM 1-α O2 is used for recombination, and low-cost Prussian blue is used to enhance the Na content. 0.44 Mn α TM 1-α The increased active sodium content in the O2 during the first charge-discharge cycle significantly improves the first-cycle charge specific capacity of the composite material, giving it an ideal first-cycle coulombic efficiency and high compatibility with the hard carbon anode in the full cell. Furthermore, this composite material fully utilizes Na... 0.44 Mn α TM 1-α O2's high discharge specific capacity and Prussian blue's high first-cycle charge specific capacity and good rate performance are combined to overcome the shortcomings of using either material alone. This achieves a synergistic improvement in the first-cycle coulombic efficiency, discharge specific capacity, energy density, rate performance, and cycle performance of sodium-ion batteries, demonstrating comprehensive performance advantages and cost-effectiveness in the actual production of sodium-ion batteries.

[0021] 2. The composite material provided by this invention not only achieves complementary advantages in performance, but also achieves superior performance through careful control of synthesis conditions in Na... 0.44 Mn α TM 1-α O2 and Na x M y [N(CN)6] z ·n A new symbiotic phase is generated at the interface of H2O. First, by controlling Na... x M y [N(CN)6] z ·n The disordered atomic packing order and the random occupation of water within the structure of the H2O crystal lead to a high-energy thermodynamically unstable state inside the crystal, resulting in localized compression or stretching, ultimately causing Na to... x M y [N(CN)6] z ·n H₂O crystals undergo structural distortion from a cubic form, resulting in abundant crystal defects. Secondly, Na… x M y [N(CN)6] z ·n The deformation regions between local slip and dislocation lines in H2O lead to stress and distortion within the crystal. Under high-energy ball milling, once the stress and distortion reach a certain level, they promote the formation of Na.x M y [N(CN)6] z ·n In H2O, M / N atoms partially replace Na in the tunnel structure. 0.44 Mn α TM 1-α The Mn / TM atoms in O2 eventually end up in Na 0.44 Mn α TM 1-α O2@Na x M y [N(CN)6] z ·n A new symbiotic phase is formed in the H2O composite material. The formation of the symbiotic phase greatly improves the first-cycle charge specific capacity of the composite material and exhibits excellent rate performance, cycle performance and energy density. Attached Figure Description

[0022] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0023] Figure 1 This is a schematic diagram of the crystal structure of the Prussian blue and tunnel oxide composite material based on the multi-dislocation crystal plane modulation in Example 1;

[0024] Figure 2 The image shows the SEM image of the Prussian blue and tunnel oxide composite material based on the multi-dislocation crystal plane modulation in Example 1.

[0025] Figure 3 The XRD patterns are of the Prussian blue and tunnel oxide composite material based on multi-dislocation crystal plane modulation in Example 1, the tunnel oxide in Comparative Example 1, and the Prussian blue with multi-dislocation crystal plane in Comparative Example 2.

[0026] Figure 4 The first charge-discharge curves of sodium-ion batteries in Example 1 and Comparative Examples 1-4 are shown.

[0027] Figure 5 The rate performance of sodium-ion batteries in Example 1 and Comparative Examples 1-4;

[0028] Figure 6 The charge-discharge specific capacity of sodium-ion batteries in Example 1 and Comparative Examples 1-4 at different rates;

[0029] Figure 7 The energy density of sodium-ion batteries at different rates in Example 1 and Comparative Examples 1-4;

[0030] Figure 8 The cycle performance of sodium-ion batteries in Example 1 and Comparative Examples 1-4 is shown. Detailed Implementation

[0031] To facilitate understanding of this invention, the invention will be described more fully and in detail below with reference to the accompanying drawings, embodiments, and comparative examples. However, the scope of protection of this invention is not limited to the following specific embodiments. Unless otherwise specified, the embodiments are performed under conventional conditions or conditions recommended by the manufacturer. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products.

[0032] Example 1

[0033] This embodiment provides a positive electrode material, a positive electrode sheet, and a sodium-ion battery, the preparation method of which is as follows:

[0034] S1: Weigh sodium carbonate and manganese trioxide at a molar ratio of 0.484:1, mix and grind thoroughly for 30 min, then fill the mixture into a mold and press it into 2 mm round discs. Place the discs in a muffle furnace and calcine at 1000 ℃ for 12 h to obtain the Na. 0.44 MnO2;

[0035] S2: Weigh 1 mol of ferrous sulfate and 1.68 mol of sodium citrate, dissolve them in 100 mL of deionized water, and stir for 3 h to prepare solution A; weigh 1 mol of sodium ferrocyanide and 2.57 mol of sodium citrate, dissolve them in 100 mL of deionized water, and stir for 2 h to prepare solution B. Then, quickly transfer solutions A and B to a constant pressure dropping funnel and a three-necked flask, respectively. Add solution A to solution B at a dropping rate of 6 drops / min. Stir the mixture at 700 rpm for 8 h and continue aging for 11 h. After aging, collect the precipitate by centrifugation at 1000 rpm and wash it three times with deionized water and ethanol, respectively. Finally, dry the washed precipitate in a vacuum oven at 120 ℃ for 12 h to obtain the multi-site dislocation Prussian blue Na. 1.55 Fe[Fe(CN)6] · 4.3H2O;

[0036] S3: Weigh Na according to a mass ratio of 3:1 0.44 MnO2 and Na 1.55 Fe[Fe(CN)6] · 4.3H2O, mixed in a ball mill at a ball-to-material ratio of 8:1 and ball-milled at 300 rpm for 5 h, can yield Na. 0.44 MnO2@Na 1.55 Fe[Fe(CN)6] · 4.3H2O.

[0037] The above Na 0.44 MnO2@Na 1.55 Fe[Fe(CN)6] · 4.3H2O composite material, Super P, and carboxymethyl cellulose (CMC) were mixed in a mass ratio of 7:2:1, and an appropriate amount of deionized water was added to prepare a slurry. The slurry was uniformly coated onto an aluminum foil current collector, dried at 80 °C overnight, and then cut to obtain the positive electrode sheet. The positive electrode sheet, sodium negative electrode sheet, and glass fiber separator were assembled into a button cell, and the inside of the cell was filled with electrolyte.

[0038] In this embodiment, the Na of the tunnel structure 0.44 MnO2 and Na with multiple dislocation crystal planes 1.55 Fe[Fe(CN)6] · The crystal structure of the symbiotic phase generated by the recombination of 4.3H2O is explained, such as... Figure 1 As shown, all PXRD data analysis was performed in Topas 5 software. First, the PXRD data was indexed to obtain unit cell, lattice parameters, and crystal symmetry information. Then, Le Bail fitting was performed on the PXRD data using the indexed cells to obtain suitable peak shapes and lattice parameters. In Example 1, Na... 0.44 The space group for MnO2 is Pmc21, a = 2.92020 Å, b = 9.22363 Å, c = 26.52522 Å. Na 1.55 Fe[Fe(CN)6] · 4.3H₂O undergoes a structural distortion from its conventional cubic structure, with Fe atoms partially replacing Na atoms. 0.44 The Mn atoms in MnO2 form a new symbiotic phase that can significantly improve the first-cycle coulombic efficiency, rate performance, cycle performance, and energy density of sodium-ion batteries.

[0039] This embodiment was characterized by SEM, such as... Figure 2 As shown, the composite material includes a tunnel structure Na 0.44 MnO2 and cubic Na with multiple dislocation crystal planes 1.55 Fe[Fe(CN)6] · 4.3H2O, its material has uniform morphology and good dispersibility.

[0040] Example 2

[0041] This embodiment provides a positive electrode material, a positive electrode sheet, and a sodium-ion battery. The difference between its preparation method and that of Embodiment 1 is that:

[0042] S1: Weigh sodium carbonate, manganese trioxide, and cobalt oxide according to a molar ratio of 0.484:0.95:0.05, mix and grind thoroughly for 40 min, then fill the mixture into a mold and press it into 2 mm round discs. Place the discs in a muffle furnace and calcine at 900 ℃ for 15 h to obtain the Na. 0.44 Mn 0.95 Co 0.05 O2;

[0043] S2: Weigh 1 mol of ferrous sulfate and 1.73 mol of sodium citrate, dissolve them in 100 mL of deionized water, and stir for 3 h to prepare solution A; weigh 1 mol of sodium cobalt cyanide and 2.32 mol of sodium citrate, dissolve them in 100 mL of deionized water, and stir for 3 h to prepare solution B. Then, quickly transfer solutions A and B to a constant pressure dropping funnel and a three-necked flask, respectively. Add solution A to solution B at a dropping rate of 6 drops / min. Stir the mixture at 700 rpm for 8 h and continue aging for 12 h. After aging, collect the precipitate by centrifugation at 1000 rpm and wash it three times with deionized water and ethanol, respectively. Finally, dry the washed precipitate in a vacuum oven at 120 ℃ for 12 h to obtain the multi-site dislocation Prussian blue Na. 1.69 Fe 0.95 [Co(CN)6] 1.12 ·3.8H2O;

[0044] S3: Weigh Na according to a mass ratio of 3:1 0.44 Mn 0.95 Co 0.05 O2 and Na 1.69 Fe 0.95 [Co(CN)6] 1.12 Na can be obtained by mixing Na with 3,8H2O at a ball mill ratio of 8:1 and ball milling at 300 rpm for 6 hours. 0.44 Mn 0.95 Co 0.05 O2@Na 1.69 Fe 0.95 [Co(CN)6] 1.12 ·3.8H2O.

[0045] Example 3

[0046] This embodiment provides a positive electrode material, a positive electrode sheet, and a sodium-ion battery. The difference between its preparation method and that of Embodiment 1 is that:

[0047] S1: Weigh sodium carbonate, manganese trioxide, and titanium dioxide according to a molar ratio of 0.484:0.95:0.05, mix and grind thoroughly for 30 min, then fill the mixture into a mold and press it into 2 mm round discs. Place the discs in a muffle furnace and calcine at 1000 ℃ for 12 h to obtain the Na. 0.44 Mn 0.95 Ti 0.05 O2;

[0048] S2: Weigh 1 mol of copper sulfate and 1.43 mol of sodium citrate, dissolve them in 100 mL of deionized water and stir for 3 h to prepare solution A; weigh 1 mol of sodium ferrocyanide and 2.65 mol of sodium citrate, dissolve them in 100 mL of deionized water and stir for 3 h to prepare solution B. Then, quickly transfer solutions A and B to a constant pressure dropping funnel and a three-necked flask, respectively. Add solution A to solution B at a dropping rate of 10 drops / min. Stir the mixture at 700 rpm for 8 h and continue aging for 15 h. After aging, collect the precipitate by centrifugation at 1000 rpm and wash it three times with deionized water and ethanol, respectively. Finally, dry the washed precipitate in a vacuum oven at 120 ℃ for 12 h to obtain the multi-site dislocation Prussian blue Na. 1.74 Cu 1.05 [Fe(CN)6] 0.86 ·3.5H2O;

[0049] S3: Weigh Na according to a mass ratio of 5:1 0.44 Mn 0.95 Ti 0.05 O2 and Na 1.74 Cu 1.05 [Fe(CN)6] 0.86 ·3.5H2O was mixed in a ball mill at a ball-to-material ratio of 10:1 and ball-milled at 300 rpm for 5 h to obtain Na. 0.44 Mn 0.95 Ti 0.05 O2@Na 1.74 Cu 1.05 [Fe(CN)6] 0.86 ·3.5H2O.

[0050] Example 4

[0051] This embodiment provides a positive electrode material, a positive electrode sheet, and a sodium-ion battery. The difference between its preparation method and that of Embodiment 1 is that:

[0052] S1: Weigh sodium carbonate, manganese trioxide, and ferric oxide according to a molar ratio of 0.484:0.9:0.1, mix and grind thoroughly for 30 min, then fill the mixture into a mold and press it into 2 mm round discs. Place the discs in a muffle furnace and calcine at 1000 ℃ for 15 h to obtain the Na. 0.44 Mn 0.9 Fe 0.1 O2;

[0053] S2: Weigh 1 mol of manganese sulfate and 2.31 mol of sodium citrate, dissolve them in 150 mL of deionized water and stir for 3 h to prepare solution A; weigh 1 mol of cuprous cyanide and 3.62 mol of sodium citrate, dissolve them in 150 mL of deionized water and stir for 3 h to prepare solution B. Then, quickly transfer solutions A and B to a constant pressure dropping funnel and a three-necked flask, respectively. Add solution A to solution B at a dropping rate of 10 drops / min. Stir the mixture at 700 rpm for 8 h and continue aging for 15 h. After aging, collect the precipitate by centrifugation at 1000 rpm and wash it three times with deionized water and ethanol, respectively. Finally, dry the washed precipitate in a vacuum oven at 120 ℃ for 12 h to obtain the multi-site dislocation Prussian blue Na. 1.67 Mn 1.13 [Cu(CN)6] 0.91 · 3.9H2O;

[0054] S3: Weigh Na according to a mass ratio of 5:1 0.44 Mn 0.9 Fe 0.1 O2 and Na 1.67 Mn 1.13 [Cu(CN)6] 0.91 · 3.9H2O was mixed with the powder at a ball mill ratio of 10:1 and ball milled at 300 rpm for 6 h to obtain Na. 0.44 Mn 0.9 Fe 0.1 O2@Na 1.67 Mn 1.13 [Cu(CN)6] 0.91 · 3.9H2O.

[0055] Comparative Example 1

[0056] Comparative Example 1 provides a positive electrode material, a positive electrode sheet, and a sodium-ion battery. The difference between its preparation method and that of Example 1 is:

[0057] Select Na in step S1 0.44 MnO2 is used as a positive electrode active material to prepare positive electrode sheets and sodium-ion batteries.

[0058] Comparative Example 2

[0059] Comparative Example 2 provides a positive electrode material, a positive electrode sheet, and a sodium-ion battery. The difference between its preparation method and that of Example 1 is:

[0060] Select Na in step S2 1.55 Fe[Fe(CN)6] · 4.3H2O is used as a positive electrode active material to prepare positive electrode sheets and sodium-ion batteries.

[0061] Comparative Example 3

[0062] Comparative Example 3 provides a positive electrode material, a positive electrode sheet, and a sodium-ion battery. The difference between its preparation method and that of Example 1 is:

[0063] Select Na in step S1 0.44 MnO2 and Na in step S2 1.55 Fe[Fe(CN)6] · 4.3H₂O was simply physically blended at a mass ratio of 3:1 to obtain Na. 0.44 MnO2-Na 1.55 Fe[Fe(CN)6] · 4.3H2O mixture was used as the positive electrode active material to prepare positive electrode sheets and sodium-ion batteries.

[0064] Comparative Example 4

[0065] Comparative Example 4 provides a positive electrode material, a positive electrode sheet, and a sodium-ion battery. The difference between its preparation method and that of Example 1 is:

[0066] Select Na in step S1 0.44 MnO2 and purchased Prussian blue reagent (PB) were subjected to high-energy ball milling in step S3 to obtain Na. 0.44 MnO2@PB composite is used as a positive electrode active material to prepare positive electrode sheets and sodium-ion batteries.

[0067] Comparative Example 5

[0068] Comparative Example 5 provides a positive electrode material, a positive electrode sheet, and a sodium-ion battery. The difference between its preparation method and that of Example 1 is:

[0069] In step S1, sodium carbonate, manganese trioxide, and molybdenum oxide are weighed in a molar ratio of 0.484:0.95:0.05, mixed, and thoroughly ground for 40 min. The mixture is then filled into a mold and pressed into 2 mm round discs. The discs are then calcined in a muffle furnace at 900 °C for 15 h to obtain the Na. 0.44 Mn 0.95 Mo 0.05O2. Na is obtained through steps S1-S3. 0.44 Mn 0.95 Mo 0.05 O2@Na 1.55 Fe[Fe(CN)6] · 4.3H2O composites are used as positive electrode active materials to prepare positive electrode sheets and sodium-ion batteries.

[0070] Comparative Example 6

[0071] Comparative Example 6 provides a positive electrode material, a positive electrode sheet, and a sodium-ion battery. The difference between its preparation method and that of Example 2 is that:

[0072] In step S2, 1 mol of ferrous sulfate and 0.65 mol of sodium citrate are weighed, dissolved in 100 mL of deionized water, and stirred for 3 h to prepare solution A. 1 mol of sodium cobalt cyanide and 0.89 mol of sodium citrate are weighed, dissolved in 100 mL of deionized water, and stirred for 3 h to prepare solution B. Na is obtained through steps S1-S3. 0.44 Mn 0.95 Co 0.05 O2@Na 0.35 Fe 0.57 [Co(CN)6] 0.63 The 5.2H2O composite was used as the positive electrode active material to prepare positive electrode sheets and sodium-ion batteries.

[0073] Comparative Example 7

[0074] Comparative Example 7 provides a positive electrode material, a positive electrode sheet, and a sodium-ion battery. The difference between its preparation method and that of Example 2 is that:

[0075] In step S2, 1 mol of ferrous sulfate and 3.75 mol of sodium citrate are weighed, dissolved in 100 mL of deionized water, and stirred for 3 h to prepare solution A. 1 mol of sodium cobalt cyanide and 4.57 mol of sodium citrate are weighed, dissolved in 100 mL of deionized water, and stirred for 3 h to prepare solution B. Na is obtained through steps S1-S3. 0.44 Mn 0.95 Co 0.05 O2@Na 3.04 Fe 1.87 [Co(CN)6] 1.43 • The 2,4H2O composite was used as the positive electrode active material to prepare positive electrode sheets and sodium-ion batteries.

[0076] Comparative Example 8

[0077] Comparative Example 8 provides a positive electrode material, a positive electrode sheet, and a sodium-ion battery. The difference between its preparation method and that of Example 3 is:

[0078] In step S3, Na is weighed at a mass ratio of 0.5:1. 0.44 Mn 0.95 Ti 0.05 O2 and Na 1.74 Cu 1.05 [Fe(CN)6] 0.86 ·3.5H₂O. Na is obtained through steps S1-S3. 0.44 Mn 0.95 Ti 0.05 O2@Na 1.74 Cu 1.05 [Fe(CN)6] 0.86 The 3.5H2O (0.5:1) composite was used as the positive electrode active material to prepare positive electrode sheets and sodium-ion batteries.

[0079] Comparative Example 9

[0080] Comparative Example 9 provides a positive electrode material, a positive electrode sheet, and a sodium-ion battery. The difference between its preparation method and that of Example 3 is:

[0081] In step S3, Na is weighed at a mass ratio of 15:1. 0.44 Mn 0.95 Ti 0.05 O2 and Na 1.74 Cu 1.05 [Fe(CN)6] 0.86 ·3.5H₂O. Na is obtained through steps S1-S3. 0.44 Mn 0.95 Ti 0.05 O2@Na 1.74 Cu 1.05 [Fe(CN)6] 0.86 The 3.5H2O (15:1) composite was used as the positive electrode active material to prepare positive electrode sheets and sodium-ion batteries.

[0082] The performance data of sodium-ion batteries in Examples 1-4 and Comparative Examples 1-9 of this invention are shown in Table 1.

[0083] Table 1. Performance data of sodium-ion batteries in Examples 1-4 and Comparative Examples 1-9

[0084]

[0085] Embodiments of the present invention utilize Na 0.44 Mn α TM 1-α O2 and Na x Fe[Fe(CN)6] ·nSodium-ion batteries prepared from H2O composite materials exhibit ideal first-cycle coulombic efficiency, high energy density at high current density, excellent rate performance, and long cycle performance. Based on the comparison results between Example 1 and Comparative Examples 1-5, it can be seen that Na… 0.44 MnO2@Na 1.55 The Fe[Fe(CN)6]·4.3H2O composite material is superior to Na+ alone. 0.44 MnO2 or Na 1.55 Fe[Fe(CN)6]·4.3H2O exhibits superior battery performance, making it suitable for a wide range of applications and common needs in real life. Furthermore, comparing the preparation method of the composite material provided by this invention with simple physical blending and commercially available Prussian blue, the composite material of this invention significantly improves its first-cycle coulombic efficiency, rate performance, and cycle performance, demonstrating the innovativeness and irreplaceability of the preparation method provided by this invention. In addition, the comparative results of Examples 6-9 show that modifications to the preparation method of this invention outside the stated scope failed to achieve the sodium-ion battery performance shown in the examples, indicating that the preparation conditions described in this invention are carefully controlled and have a synergistic effect in improving performance.

[0086] By comparison Figure 3 The XRD patterns of Example 1, Comparative Example 1, and Comparative Example 2 show that the Na in Example 1... 0.44 MnO2@Na 1.55 The Fe[Fe(CN)6]·4.3H2O complex not only possesses the Na content of Comparative Example 1, but also... 0.44 MnO and Na from Comparative Example 2 1.55 The compound exhibits characteristic peaks of Fe[Fe(CN)6]·4.3H2O, and new characteristic peaks appear at 12.6°, 15.6° and 25.3°, indicating that a new symbiotic phase has emerged in the compound of Example 1.

[0087] comprehensive Figure 4-8 Comparing the first-cycle charge-discharge specific capacity, energy density, rate performance, and cycle performance of Example 1 with Comparative Examples 1-5, the following conclusions can be drawn: 1) Na of Comparative Example 1 0.44 While MnO2 exhibits a high initial discharge capacity, it suffers from a low initial charge capacity and poor rate performance. In contrast, Na (comparative example 2)... 1.55Fe[Fe(CN)6]·4.3H2O possesses ideal first-cycle coulombic efficiency and rate performance, but its first-cycle discharge specific capacity is poor. Therefore, the composite material in Example 1 of this invention not only combines the advantages of the two materials mentioned above but also overcomes their shortcomings. 2) The results of Comparative Example 3 demonstrate that simply physical blending the two materials mentioned above is insufficient to achieve superior battery performance. Therefore, the composite preparation method provided by this invention generates a new symbiotic phase. The unique structure of this composite is innovative and difficult to replace or achieve using conventional methods. 3) The results of Comparative Example 4 demonstrate that replacing the Prussian blue with commercially available PB instead of the multi-dislocation crystal plane provided by this invention, and combining it with Na... 0.44 The composite material prepared with MnO2 also failed to achieve the battery performance shown in Example 1, indicating that the Prussian blue with multiple dislocation crystal planes provided by this invention has a unique structure and excellent performance. 4) The results of Comparative Example 5 demonstrate that the scope of this invention plays a synergistic role in various aspects, and is the result of careful selection.

[0088] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A universal method for controlling the composition of Prussian blue and tunnel oxide composite materials, characterized in that, The chemical formula of the composite material is Na. 0.44 Mn α TM 1-α O2@Na x M y [N(CN)6] z ·n H2O, in which the M / N atoms in the Prussian blue partially replace the TM atoms in the tunnel oxide, promotes the formation of a new symbiotic phase in the composite material. The specific synthesis steps are as follows: S1: Weigh out sodium carbonate and transition metal oxide in a certain stoichiometric ratio, mix and grind thoroughly for 30-60 min, then fill the mixture into a mold and press it into 2-5 mm round discs; place the discs in a muffle furnace and calcine at 800-1000 ℃ for 10-20 h to obtain the Na. 0.44 Mn α TM 1-α O2, where 0 ≤ α ≤ 1; S2: Dissolve transition metal sulfate and sodium citrate in 50-200 mL of deionized water at a specific molar ratio and stir for a certain time to prepare solution A. Dissolve the transition metal complex and sodium citrate in 50-200 mL of deionized water at a specific molar ratio and stir for a certain time to prepare solution B. Then, quickly transfer solutions A and B to a constant pressure dropping funnel and a three-necked flask, respectively. Add solution A dropwise to solution B. Stir the resulting mixed solution at 500-1200 rpm for a certain time and continue aging. After aging, collect the precipitate by centrifugation at 800-1500 rpm and wash it 3-5 times with deionized water and ethanol, respectively. Finally, dry the washed precipitate in a vacuum oven at 100-150 ℃ for 10-20 h to obtain Prussian blue Na with multiple fault planes. x M y [N(CN)6] z ·n H2O; S3: Weigh out a certain mass ratio of Na 0.44 Mn α TM 1-α O2 and Na x M y [N(CN)6] z ·n H2O is mixed with the material in a ball mill at a certain ball-to-material ratio and milled at 200-500 rpm for 2-8 hours to obtain Na. 0.44 Mn α TM 1-α O2@Na x M y [N(CN)6] z ·n H2O; The transition metal element TM in the transition metal oxide mentioned in step S1 is any one of the elements in Group IVB or VIII of the third period, or a mixture of multiple elements in stoichiometric ratio. The stoichiometric ratio of sodium carbonate to the transition metal oxide is based on Na... 0.44 Mn α TM 1-α The molar ratio of the chemical composition of O2, in which sodium carbonate is in excess by 7-20%; The transition metal sulfate, transition metal complex and Na mentioned in step S2 x M y [N(CN)6] z ·n The transition metal element M / N in H2O is any one of the elements in Group VIII or IB of the third period, or a mixture of multiple elements in stoichiometric ratios, and the ligand of the transition metal complex is CN. - ; In step S2, the molar ratio of the transition metal sulfate to sodium citrate is 1:0.8-1:3.5, and the stirring time is 1-5 hours; the molar ratio of the transition metal complex to sodium citrate is 1:1.2-1:4.3; the Prussian blue Na... x M y [N(CN)6] z ·n 0.53≤ in H2O x ≤2.68, 0.65≤ y ≤1.75, 0.85≤ z ≤1.35, 2.7≤ n ≤4.6; Na mentioned in step S3 0.44 Mn α TM 1-α O2 and Na x M y [N(CN)6] z ·n The mass ratio of H2O is 2:1-10:

1.

2. The universal method for controlling the composition of Prussian blue and tunnel oxide composite materials according to claim 1, characterized in that, In step S2, the dropping rate of solution A is controlled at 1-10 drops / minute, the stirring time of the mixed solution is 5-10 hours, and the aging time is 10-16 hours.

3. The universal method for controlling the composition of Prussian blue and tunnel oxide composite materials according to claim 1, characterized in that, In step S3, the ratio of grinding balls to material in the ball mill is 6:1 to 15:1.

Citation Information

Patent Citations

  • Magnesium-doped ternary layered positive electrode material for sodium ion battery and preparation method of magnesium-doped ternary layered positive electrode material

    CN115498156A

  • A sodium-ion cathode material and its preparation method and sodium-ion batteries

    CN116364898B

  • Prussian blue compound coated sodium ion battery positive electrode material and preparation method and application thereof

    CN115312719A

  • Prussian blue-like transition metal cyanide, preparation method therefor, and related positive electrode plate, secondary battery, battery module, battery pack and device

    US20230227321A1